Gut microbiome in intracranial aneurysm growth, subarachnoid hemorrhage, and cerebral vasospasm: a systematic review with a narrative synthesis - Klepinowski, Tomasz; Skonieczna-Żydecka, Karolina; Pala, Bartłomiej; Stachowska, Ewa; Sagan, Leszek (Frontiers in Neuroscience, 2023)
Intracranial aneurysms (IA) are the most common cerebral vascular pathologies. Their rupture leads to the most dangerous subtype of stroke – aneurysmal subarachnoid hemorrhage (aSAH), which may be followed by cerebral vasospasm and ischemic sequelae. Recently, an imbalance within the gutintestinal microbiota, referred to as dysbiosis, was suggested to play a role in formation, progression, and rupture of IA. As no systematic review on this topic exists, considering the significance of this matter and lack of effective prophylaxis against IA or cerebral vasospasm, we aim to sum up the current knowledge regarding their associations with intestinal microbiome, identify the gaps, and determine future prospects. Scientific databases were systematically and independently searched by two authors from inception to 1st May 2023 for original articles regarding the role of gutintestinal microbiota in intracranial aneurysmal growth, aSAH occurrence, as well as in cerebral vasospasm following aSAH. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist was followed in an abstraction process. STROBE tool was applied to assess the risk of bias. This research was funded by National Science Centre, Poland. Grant number 2021/41/N/NZ2/00844. Of 302 records, four papers were included that fully met eligibility criteria. Studies reported (1) relative abundance of Hungatella hathewayi is a protective factor for aneurysm growth and rupture, resulting from the reduced inflammation and extracellular matrix remodeling in cerebral arterial wall, and from reduced metalloproteinase-mediated degradation of smooth muscle cells in cerebral vessels. (2) Relative abundance of Campylobacter ureolyticus is associated with aSAH. (3) No article has evaluated microbiota in relation to cerebral vasospasm following aSAH, although there is an ongoing study. We concluded that gutintestinal microbiota might be a potential target for diagnostic and therapeutic tools to improve management of cerebral aneurysms. However, more studies of prospective design are needed.